Magical thinking in psychology; professors´ representations - López De Pomar, Fabrizio (2019)
Universities are education centers that promote scientific training. Several studies have questioned the presence of magical thinking in students attending undergraduate programs in science such as psychology students. Using a strategy different from the quantitative approach in university students of the psychology undergraduate program, this research aimed to contribute to this line of work. Psychology professors’ representations of magical thinking in psychology training and career were analyzed using a qualitative approach. Semi-structured interviews were performed, and the collected information was organized in topics, categories and subcategories. The discussion addresses the agreements and disagreements found on professors’ understanding of science, psychology, their scope and limits.